CONSUMER PROTECTION REGARDING ONLINE LOAN CARTELS IBNU TAIMIYAH'S PERSPECTIVE - Hafiza Husna Ayub; Tetty Marlina Tarigan (Journal of International Islamic Law, Human Right and Public Policy, 2024)
The main problem and research is consumer protection in fintech agreements (online loans) viewed from the perspective of Ibnu Taimiyah and positive law, namely based on POJK, and looking at the extent to which consumer protection has been regulated in Islamic law and positive law. The type of research in writing this thesis uses normative legal research, with a qualitative approach and the data sources used are primary data sources and secondary data sources with data collection techniques in the form of library studies. From the research conducted by the author, it can be concluded thatIbnu Tamiyah's perspective on consumer protection regarding online loan cartels highlights the importance of justice, equality and rejection of exploitation in economic transactions. Through Islamic moral and ethical principles, Ibnu Tamiyah emphasized the need to ensure that business practices do not harm or exploit consumers, and that all parties involved in economic transactions have equal and fair access. Consumer protection from Ibnu Tamiyah's perspective also emphasizes the importance of complying with applicable laws and increasing consumer education and awareness about their rights.Existing fintech (online loan) agreements have not been able to fully protect consumer rights and obligations in accordance with existing legal regulations such as the MUI DSN Fatwa Number 117. Because currently only one regulation for sharia fintech has been used as a source. The main law is the MUI DSN Fatwa Number 117 of 2018 concerning Information Technology-Based Financing Services Based on Sharia Principles. Meanwhile, consumer protection in positive law is based on POJK Number 77 of 2016 and POJK Number 13 of 2018. The author found the fact that the OJK Regulation on Consumer Protection in the financial services sector actually provides protection and in it guarantees order, certainty and justice for consumers, but POJK only regulates one aspects of the online loan agreement, namely conventional online loans.